Toward Fundamental Fairness in the Kangaroo Courtroom: The Due Process Case Against Statutes Presumptively Closing Juvenile Proceedings - Oestreicher, Stephen E. (2001)
Today's juvenile courtroom functions quite differently than did its 1899 Chicago ancestor. During every decade since the 1960s, the juvenile court system has undergone a number of fundamental, structural changes. The most recent of these mega change[s] came during the 1990s, when a number of states abandoned their existing presumptive closure statutes and mandated that juvenile delinquency proceedings be held in the open for the press and the public to see. The policy reviews of this development have been mixed. Some commentators criticize the recent trend, asserting that open proceedings enervate the juvenile system's ultimate goal of rehabilitating wayward youths. Others laud the new openness, arguing that closure no longer serves the rehabilitative ethic, or that young offenders need to be held accountable to the body politic for their increasingly violent and adult-like wrongs against society. This Note also praises the trend toward openness, but it takes a different tack than do these commentators; it suggests, as the United States Supreme Court suggested in Oliver, that if a person's liberty is at stake, public scrutiny is the only tolerably efficient check against potential abuse or malfunction of the adjudicative process. It argues that, aside from the states' policy-based reasons for abandoning presumptive closure statutes, serious due process problems inhere in presumptive closure schemes. Thus, this Note does not concern itself with the states that have recently overturned their presumptive closure statutes; it instead turns its attention toward the nineteen jurisdictions that retain theirs. This Note concludes that the nineteen remaining presumptive closure statutes are unconstitutional because they violate the Due Process Clause of the Fourteenth Amendment. The argument proceeds in two major Parts. Part I lays the necessary factual groundwork for the case against the statutes by describing how they affect today's juvenile proceedings. Part II introduces and evaluates three separate-but related-constitutional challenges to the statutes. That is, it briefly acknowledges and rejects First Amendment and Sixth Amendment arguments, and it then raises a freestanding Fourteenth Amendment due process argument. Part II suggests that, while both the First and Sixth Amendment arguments could reasonably be brought to bear on presumptive closure statutes, only the freestanding due process claim has a strong chance of succeeding under existing Supreme Court jurisprudence. This Note concludes that the statutes are fundamentally unfair under that jurisprudence and can no longer withstand constitutional scrutiny